Outcomes of an Underserved Hispanic Population with Chronic Hepatitis C treated with Pegylated-Interferon and Ribavirin in a Government-Sponsored Clinic - Iturrino, Johanna; Sánchez, Carlos J.; Ortiz, Adelaida; Romero, Carlos J.; Velázquez, Vanessa; Costas, Pablo; Torres, Esther A. (Puerto Rico Health Sciences Journal, 2011)
Objective: Treatment of hepatitis C virus (HCV) with interferon-based therapy has been shown to be less effective in Hispanics when compared to other populations. A pilot clinic was established at the University of Puerto Rico for the treatment of HCV in the government-insured population. The aim of this study was to describe the outcomes and treatment response to pegylated interferon and ribavirin in treatmentnaïve patients enrolled at this government sponsored clinic. Methods: A retrospective analysis was undertaken to investigate the treatment outcomes with weight based peg-interferon-alfa-2b and ribavirin in patients with chronic HCV enrolled in the pilot clinic during 2003-2005. Descriptive statistics were reported. Continuous variables were summarized as means and standard deviations. Frequency distributions and percents were used for categorical variables. Statistical analysis was performed using STATA. Results: A total of 155 patients (105 males and 50 females) with mean age of 42 years started treatment; 79 (51%) patients had HCV genotype 1. Completion of treatment was achieved by 59 patients (38.1%), of whom end of treatment response (ETR) was observed in 30 (50.9%), representing 19.4% of the intention-totreat population (ITT). Sustained viral response (SVR) was achieved in 17 (28.8%) patients who completed treatment, resulting in 11% (17/155) SVR by ITT. The only significant predictor of SVR was treatment onset within 5 years of the diagnosis of HCV (p=0.026). Although no association was found between HCV genotype and SVR (p=0.192), those patients with HCV genotypes 2 and 3 were more likely to complete treatment (p=0.009). Conclusion: SVR to pegylated interferon and ribavirin seems to be lower than expected in our population. The high rate of incomplete treatment surpasses previously reported rates in U.S. Latinos and Caucasians. Further studies should explore reasons for lower response and higher treatment discontinuation in our population.